Adverse effects of chemical UV filters - Bogusława Budziszewska; Beata Starek-Świechowicz; Żaneta Broniowska; Alicja Maciejska (Polish Pharmaceutical Society, 2021)
Chemical UV filters can cause irritation or allergic contact dermatitis, but also when absorbed into the blood, they can interfere with some body functions. The current data indicate the influence of these compounds on the gonadal function, the activity of the hypothalamic-pituitary-thyroid axis as well as the viability of nerve cells. Most of the data concern the adverse effects of benzophenone-3 [2-hydroxy-4-methoxybenzophenone; BP-3], benzophenone-2 [2,2 ', 4,4'-tetrahydroxybenzophenone; BP-2], a camphor derivative [3- (4-methylbenzylidene) camphor; 4-MBC] and a cinnamate derivative [octyl methoxycinnamate; OMC]. The main and so far the best known effect of some UV filters, including BP-3, BP-2, 4-MBC and OMC, is to affect sex hormone receptors and disrupt the gonadal function. For this reason, these compounds are included in the group of Endocrine Disrupter Compounds (EDCs). In vitro studies have shown their agonist activity at estrogen receptors and antagonist activity at the androgen and progesterone receptors. The estrogenic activity of these compounds and their unfavorable effect on testicular function in male rats and uterine weight and oestrus cycle disturbances in females were also demonstrated in vivo. Data on the influence of these compounds on thyroid function are not conclusive, as their effect depends on the model used and the route of administration. The neurotoxic effect of BP-3 was demonstrated in male rats, but no such effect was found for BP-2, while the neurotoxic effects of 4-MBC and OMC have not been studied. Changes in the reproductive organs after exposure to these filters and the neurotoxic effects of BP-3 were observed in adult animals mainly in developmental studies or in animals exposed to the test compound also in the prenatal period. Differences depending on sex and route of administration of the compound were also observed. In the light of the research conducted so far, it cannot be ruled out that the increasing use of certain chemical UV filters, especially with simultaneous exposure to other compounds from the EDCs group, may be one of the causes of decreased fertility in humans, more and more frequent disorders of the thyroid gland and disturbances of the central nervous system (CNS).